2020
DOI: 10.15547/ast.2020.03.042
|View full text |Cite
|
Sign up to set email alerts
|

Some physical properties of lentil seeds affected by harvest time

Abstract: The physical properties and the hardness of lentil seeds, which can also be affected by harvest times, are very important variables in the designing and adjustment of machineries used during harvest, handling and other processes. The objective of this study is to determine the effects of different harvest times on some physical and mechanical properties of lentil seeds. A field experiment was conducted at six harvest times including the harvesting at physiological maturity (H1) and 5, 10, 15, 20 and 25 days af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…The geometric and arithmetic diameters of the red lentils (3.77 mm and 3.42 mm, respectively) were much smaller than the yellow peas (6.61 mm and 6.48 mm, respectively). The arithmetic and geometric mean diameters, and sphericity values of red lentil variety: Seyran-96 from the study conducted by Gürsoy and Güzel [23] matches with the results of red lentils in present study. The higher sphericity value for yellow peas (92.99%) compared to red lentils (76.54%) suggests that the shape of yellow peas tends to be more spherical in nature.…”
Section: Grain Characteristicssupporting
confidence: 89%
“…The geometric and arithmetic diameters of the red lentils (3.77 mm and 3.42 mm, respectively) were much smaller than the yellow peas (6.61 mm and 6.48 mm, respectively). The arithmetic and geometric mean diameters, and sphericity values of red lentil variety: Seyran-96 from the study conducted by Gürsoy and Güzel [23] matches with the results of red lentils in present study. The higher sphericity value for yellow peas (92.99%) compared to red lentils (76.54%) suggests that the shape of yellow peas tends to be more spherical in nature.…”
Section: Grain Characteristicssupporting
confidence: 89%
“…This indicated that the shape was close to spherical. Sphericity values were found in the range of 53.3-58.7% for wheat varieties, 44.4-45.8% for the barley variety, 73.5-78.0% for the lentil variety, and 86.3-89.8% for the chickpea variety (Gürsoy & Güzel, 2010).…”
Section: The Dimensions Of Seedmentioning
confidence: 95%